2010
DOI: 10.1080/09500790.2010.519024
|View full text |Cite
|
Sign up to set email alerts
|

Reflection in example- and problem-based learning: effects of reflection prompts, feedback and cooperative learning

Abstract: To examine the effects of reflection prompts, elaborated feedback and cooperation on learning and reflection, two experimental studies were conducted. For both studies, an example-and problem-based e-learning environment on correlation was used. In Study 1, 57 university students were randomly assigned to two conditions: with reflection prompts that asked students to give reasons for their decisions and without reflection prompts. The intervention promoted learning, and the students' reasons indicated substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
1
16
0
3
Order By: Relevance
“…They can ask critical and reflective questions to evoke students' reflection and ultimately transfer of knowledge, skills and attitudes, also known as prompting via specific reflective prompts. Prompts are verbal or written stimuli that foster students to justify their decisions in the learning process, in analogy to thinking-aloud protocols, for example when students were asked to type short reasons for each decision (Krause and Stark 2010). Krause and Stark (2010) show that when such prompts are combined with elaborated feedback, deeper levels of reflection facilitate learning, which is "especially promising for students with little prior knowledge, low confidence or low motivation concerning the respective field" (p. 269).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can ask critical and reflective questions to evoke students' reflection and ultimately transfer of knowledge, skills and attitudes, also known as prompting via specific reflective prompts. Prompts are verbal or written stimuli that foster students to justify their decisions in the learning process, in analogy to thinking-aloud protocols, for example when students were asked to type short reasons for each decision (Krause and Stark 2010). Krause and Stark (2010) show that when such prompts are combined with elaborated feedback, deeper levels of reflection facilitate learning, which is "especially promising for students with little prior knowledge, low confidence or low motivation concerning the respective field" (p. 269).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Prompts are verbal or written stimuli that foster students to justify their decisions in the learning process, in analogy to thinking-aloud protocols, for example when students were asked to type short reasons for each decision (Krause and Stark 2010). Krause and Stark (2010) show that when such prompts are combined with elaborated feedback, deeper levels of reflection facilitate learning, which is "especially promising for students with little prior knowledge, low confidence or low motivation concerning the respective field" (p. 269). Moreover, students' reflection is a prerequisite for accommodation and expansive learning (Illeris 2004).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Diversity of group members was suggested in some research to increase creativity and positively affect team performance (Amabile, 1989), whereas in other research it was also shown to possibly trigger negative affective reactions and withdrawal of some group members (Ely, 1994;Maznevski, 1994). Similar mixed results appear on the relationship of sex composition, group size and group performance (Ely & Thomas, 2001;Krause & Stark, 2010;Orlitzky & Benjamin, 2003).…”
Section: Literature Reviewmentioning
confidence: 64%
“…Such acts of domination may result in withdrawal of others from collaboration and thus hinder learning. This may especially happen in a statistics course (Krause & Stark, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation